2010
DOI: 10.1002/star.200900260
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of cooked‐rice nutritionally important starch fractions with other physicochemical properties

Abstract: Sixteen rice cultivars representing five cytosine-thymine repeat (CT n ) microsatellite genetic marker groups were analyzed for their cooked rice nutritionally important starch fractions (NISFs, which include rapidly digestible (RDS), slowly digestible (SDS), and resistant starch (RS)), basic grain quality indices (apparent amylose (AM), crude protein (CP), alkali spreading value (AS), and gel consistency (GC)), pasting characteristics, and thermal properties. Chemometric tools (bivariate correlation, principa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…In addition, a positive correlation (r = 0.77604, p < 0.05) between amylose and SDS contents was observed. Patindol et al (2010) and Chung et al (2011) also reported a positive correlation between amylose and RS contents of rice varieties. Besides, Chung et al (2011) obtained a positive correlation between amylose and SDS contents of rice starches.…”
Section: Starch Fractions and Amylosementioning
confidence: 76%
“…In addition, a positive correlation (r = 0.77604, p < 0.05) between amylose and SDS contents was observed. Patindol et al (2010) and Chung et al (2011) also reported a positive correlation between amylose and RS contents of rice varieties. Besides, Chung et al (2011) obtained a positive correlation between amylose and SDS contents of rice starches.…”
Section: Starch Fractions and Amylosementioning
confidence: 76%
“…Total starch (TS) values were obtained using minced (with a garlic press) freshly cooked rice and a TS kit (Megazyme, Wicklow, Ireland). The analysis of the rapidly digestible starch (RDS), slowly digestible starch (SDS), and resistant starch (RS) was performed according to the Englyst et al (1992) method with modifications (Patindol et al 2010c). In a 50-mL graduate conical, screwcap centrifuge tube, 1 g of minced freshly cooked rice sample (in triplicate) was weighed, and 50 mg of guar gum, a 12.7 × 3 mm magnetic stir bar, and 20 mL of acetate buffer (0.1M, pH 5.2) were added.…”
Section: Measurement Of Nutritionally Important Starch Fractionsmentioning
confidence: 99%
“…However, no study has been published regarding detection of physicochemical properties of Indonesian indica rice using DNA markers. Most markers for physicochemical properties determining palatability/cooking quality have been developed based on polymorphic and association analyses (Bao et al 2006a,b;Patindol et al 2010;Zhao et al 2012). By using molecular markers developed for japonica and indica genomes, predicting physicochemical properties of indica rice should be much more efficient.…”
Section: Introductionmentioning
confidence: 99%